Transient Receptor Potential Vanilloid-1 (TRPV1) Alleviates Hepatic Fibrosis via TGF-β Signaling. (21st July 2022) - Qian, Ke; Lei, Xiaohua; Liu, Guoxing; Fang, Yu; Xie, Chengzhi; Wu, Xiaolong; Liu, Qiang; Liu, Gao; Cao, Zhenyu; Zhang, Ju; Kuang, Tao; Yan, Likun; et al.
Abstract : Hepatic fibrosis is a major global health problem and considered a leading cause of liver-related morbidity and mortality worldwide. Although previous studies have suggested that transient receptor potential vanilloid-1 (TRPV1) is protective against cardiac and renal fibrosis, its functional role in hepatic fibrosis has remained elusive. Herein, we characterize the effects of TRPV1 on carbon tetrachloride- (CCl4 -) induced mice, in vitro transforming growth factor- β - (TGF- β -) treated hepatic stellate cells (HSCs), and human fibrosis specimens. Finally, our results demonstrated the significant TRPV1 downregulation in human liver fibrosis tissues. Knocking out TRPV1 significantly increased the expression of various hepatic fibrosis markers, while the expression of these biomarkers declined markedly in capsaicin-activated mice. Moreover, our study revealed that knocking down TRPV1 would enhance the promotive effect of TGF- β on HSC proliferation, cell cycle, cell apoptosis, and ECM expression. Also, such promotive effect can be partially reversible by capsaicin, an exogenous activator of TRPV1. Collectively, the obtained data suggest that TRPV1 may alleviate CCl4 -induced hepatic fibrosis and attenuate the effect of TGF- β on HSC activation, proliferation, and apoptosis, which overall implies that targeting TRPV1 channel activity may be an effective therapeutic strategy for treating hepatic fibrosis.